Role of Pancreatic Attenuation Index in Assessing Pancreatic Fat Content and Postpancreatectomy Outcomes - Perikinchira, Rizwan Ahmed; Rajan, Ramesh; P., Bonny Natesan; Gisuthan, Bindiya; Jayasree, L.; K.S, Swasthik; Subramanian, Santhoshkumar; Antony, Agestino V. (Indian Journal of Radiology and Imaging, 2023)
Background High fat content of pancreas can contribute to its soft texture, which is a strong predictor for postoperative pancreatic fistula (POPF). We propose to assess the relationship of pancreatic computed tomography (CT) attenuation index (PAI) with histopathological fat content of pancreas and postpancreatectomy outcomes.Methodology Data was collected prospectively from patients who underwent pancreatic resections from February 2021 to January 2023. CT attenuation was measured in pancreas and spleen in three regions of interest each. The mean of the three values was taken as the mean pancreatic attenuation (P) and splenic attenuation(S). PAI was calculated (P-S and P/S) preoperatively. The fat content was calculated histologically in resected specimens. The pancreatic texture was also assessed intraoperatively by the operating surgeon to classify it as soft or firm. The relationship of PAI with fat content and postpancreatectomy outcomes such as delayed gastric emptying (DGE), postpancreatectomy hemorrhage (PPH) and POPF was assessed.Results Seventy patients underwent pancreatic resections of which 59 were taken for analysis after satisfying the exclusion criteria. The PAI ranged from P-S (-23 to +19) and P/S (0.54–1.5). The histologic fat content of pancreas ranged from 0.4 to 42% (mean= 9.5076/standard deviation: 9.19520). Significant correlation was found between P-S and P/S (Spearman's rank correlation coefficient ρ = –0.775[95% confidence interval [CI]: –0.919 to –0.583], –0.743[95% CI: –0.896 to –0.467]) with pancreatic fat content. Postpancreatectomy outcomes noted were POPF(B/C):13, DGE:33, and PPH:3. Statistical significance was not seen between PAI and postpancreatectomy outcomes (POPF, p = 0.067 DGE; p = 0.456; PPH, p = 0.891).Conclusion PAI may be used as a reliable tool in predicting pancreatic fat content. However, it did not show a statistically significant association in predicting postpancreatectomy outcomes.
Keywords: pancreatic attenuation index; postoperative pancreatic fistula; pancreatic steatosis